The Academic Response to COVID-19 - Chantelle Rijs; Frederick Fenter (Frontiers Media S.A., 2020)
COVID-19 has posed an unprecedented challenge to the international scientific community. Along with the disruption faced by most of the world's population, many researchers have felt an added pressure to understand, cure and mitigate the virus. In order to gain insight into what impact COVID-19 has had on the international scientific community, their work and the implications for science, we conducted a survey with our editors, reviewers and authors in May and June 2020. In one of the largest academic surveys ever conducted, 25,307 members of our academic community participated, representing diverse countries, roles, and areas of research.